Perancangan Sistem Keamanan Tambahan Pada Kendaraan Menggunakan Tracker SMS - Herlambang Agung Pangestu; R. Tommy Gumelar; Shevti Arbekti Arman (ITB Ahmad Dahlan Jakarta, 2023)
Motor vehicle theft continues to pose a significant issue, primarily due to the vulnerability of security systems relying on manual keys. Thieves are well-versed in exploiting this weakness, necessitating innovative solutions. This study's objective is to design a tool that employs a GPS tracker and SMS to provide precise location coordinates. Additionally, it aims to deter motor vehicle theft by interrupting the electric current flow in the vehicle. Using the Research and Development (R&D) method based on prior research, the outcome is a system capable of providing location points at extensive distances beyond conventional vehicle boundaries. In summary, this device interacts by sending pre-programmed commands to Arduino Uno, with ON functioning to activate electrical systems, OFF for deactivation, and LOCATION for requesting navigational position messages.